Harnessing the power of dialogue: examining the impact of facebook content on citizens' engagement. Issue 1 (2nd January 2022) - Lappas, Georgios; Triantafillidou, Amalia; Kani, Anastasia
ABSTRACT: The present study sheds light on the under-researched relationship between social media content and citizens' engagement, as well as the impact of dialogic communication on citizens' engagement. To this end, Facebook content of the five largest Greek municipalities was examined. A six-dimensional typology of social media content posted by local governments on Facebook was proposed. The results suggest that dialogic posts and posts that trigger offline participatory activities exerted significant influence on all forms of citizens' online engagement. It is recommended that social media managers of local governments in Greece, as well as other countries with similar public administration styles and social media usage patterns, create dialogic loops with their citizenry by addressing users' questions and concerns through Facebook posts. Moreover, they could publish rich media content on Facebook in the form of videos and posts that mobilise citizens to participate in various offline activities (e.g., events, council meetings).